ANALISIS STABILITAS LERENG BATUAN DENGAN METODE SLOPE STABILITY PROBABILITY CLASSIFICATION (SSPC) PADA KAWASAN PIYUNGAN-PATUK, DAERAH ISTIMEWA YOGYAKARTA - Rana Wiratama (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2018)
Landslide events in an area are manifestations of unstable slope conditions, so that evaluation of slope stability and mapping of areas prone to landslides is very important as an effort to mitigate landslides. In this study the Slope Stability Probability Classification (SSPC) method was used to evaluate slope stability in the Piyungan-Patuk area. which is a rock mass classification system for slope stability which classifies 3 (three) different rock masses through a three-step approach namely: Exposure Rock Mass (ERM), Reference Rock Mass (RRM) and Slope Rock Mass (SRM). Slope stability analysis results on 18 selected slopes obtained probability of slope stability with very low to very high classification with a probability value of stability <0.5 to> 95, where the probability value is strongly influenced by rock mass parameters such as rock strength, discontinuity and weathering rate .